Unilateral Lobe Resection by Video-Assisted Thoracoscopy Leads to the Most Optimal Functional Improvement in Severe Emphysema - Beckers, Frank; Lange, Nadine; Koryllos, Aris; Picchioni, Fabrizio; Windisch, Wolfram; Stoelben, Erich (The Thoracic and Cardiovascular Surgeon, 2016)
Background Lung volume reduction surgery (LVRS) is a well-established treatment option for pulmonary emphysema, but the most advantageous technical approach remains debatable.Methods Short- and long-term outcomes were comparably assessed in pulmonary emphysema patients who underwent unilateral LVRS with either lobe or sublobe (segment or wedge) resection. Patients were consecutively enrolled in the study after careful conventional and computer-based definition of the target region.Results A total of 36 patients with a mean age of 62.1 ± 8.9 years (range, 41–79 years) were recruited. Video-assisted thoracoscopy (VATS) was performed in 33 patients, while 3 patients with additional early-stage lung cancer received anterolateral thoracotomy. Surgery duration was longer for lobectomy (median 93 minutes, range 44–168 minutes) as compared with sublobe resection (median 52 minutes, range 25–131 minutes; p = 0.0007), but complication rates were similar. After 90 days postsurgery, mortality was zero and lung function improved to a similar degree in both the groups. After 1 year, total lung capacity (TLC) was still reduced by 17.2 ± 20.6% predicted as compared with the baseline values for lobe resection, while TLC was increased by 12.1 ± 14.5% predicted for sublobe resection. In addition, the 6-minute walking distance improved following LVRS, with slightly better results in lobe resection patients.Conclusions By careful definition of the target region, unilateral VATS-LVRS with lobe resection in severely affected pulmonary emphysema patients is a safe procedure that is superior to unilateral sublobe VATS resection in terms of improving long-term 1-year lung hyperinflation. Therefore, unilateral VATS lobe resection is a promising treatment approach that should be further evaluated by randomized controlled trials.
Keywords: emphysema; bullae; lung benign lesion; congenital lesion; pulmonary function; surgery complication; surgery incisions; thoracoscopy; VATS